2008
DOI: 10.1016/s0301-0546(08)75222-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of mast cells in benign and malignant colonic lesions: immunohistochemical study on formalin-fixed, paraffin-embedded tissues

Abstract: We were the first to analyse mast cells in the active stage and in remission in the same patients with ulcerative colitis using immunohisto-chemical methods, and compared the number of mast cells between benign and malignant colonic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…One evidence of the mast cells involvement in neoplasm development is the presence of a greater number of mast cells in malignant human breast tumors than in benign tumors (Kashiwase et al, 2004) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One evidence of the mast cells involvement in neoplasm development is the presence of a greater number of mast cells in malignant human breast tumors than in benign tumors (Kashiwase et al, 2004) .…”
Section: Resultsmentioning
confidence: 99%
“…Several epidemiological, clinical, and experimental studies have demonstrated an association between chronic inflammation and cancer, in which inflammatory mediators contribute to the progression of the illness (Murdoch et al, 2008). According to Ranieri et al (2003) (Imada et al, 2000;Elpek et al, 2001;Weidner et al, 2001;Kashiwase et al, 2004). The contribution of mast cells to angiogenesis in human tumors is clear but not well established (Murdoch et al, 2008), in veterinary medicine, however, there is no study in the literature with this information.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mast cells in the stroma with infiltration of inflammatory cells is an early effect of carcinogen administration in mammary gland carcinogenesis (13). Correspondingly, in human breast biopsies the number of mast cells is significantly increased in malignant tumours as compared to benign lesions (8). Mastocytes accumulate in response to the numerous chemoattractants (27) such as regulated on activation, normal T-cell expressed and secreted (RANTES) or monocyte chemotactic protein-1 (MCP-1), and are associated with poor prognosis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Whether adipose-derived contractile mediators may contribute to the so-called "adventitial shrinkage" due to myofibroblast contraction in postangioplasty coronary restenosis (80), remains to be studied It is known that inflammation can promote cancerogenesis (47)(48)(49)(50). There is compelling evidence indicating that both normal mammary gland development and breast cancer growth depend, in part, on a microenvironment, of which adipose tissue is a key component.…”
Section: Vasoconstrictorsmentioning
confidence: 99%
“…Breast cancer is commonly associated with a prominent immune, especially mast cell, response (2,50). Both adipocytes and mast cells produce various factors known to upregulate aromatase expression; moreover, mast cell-derived tryptase is a potent stimulator of both angiogenesis and fibroblast proliferation (reviewed in 2, 4).…”
Section: Vasoconstrictorsmentioning
confidence: 99%